Gastrocolocutaneous fistula: An undetected complication of colon transfixation during percutaneous endoscopic gastrostomy - Nunes, Gonçalo; Oliveira, Gabriel; Cortez-Pinto, João; Cruz, João; Fonseca, Jorge (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Nunes G, Oliveira G, Cortez-Pinto J, Cruz J, Fonseca J. Gastrocolocutaneous fistula: An undetected complication of colon transfixation during percutaneous endoscopic gastrostomy. Turk J Gastroenterol 2019; 30(8): 761-3.